4x^3 - 12x^2 - 9x + 27 = 0
4x^2(x - 3) - 9(x - 3) = 0
(4x^2 - 9)(x - 3) = 0
(2x + 3)(2x - 3)(x - 3) = 0
x = {-3/2, 3/2, 3}
2007-01-11 11:25:03
·
answer #1
·
answered by Helmut 7
·
1⤊
1⤋
Difference of Squares formula:
(a^2 - b^2) = (a-b)(a+b)
first move everything to the left side of the equation:
(4x^3 - 12x^2) - (9x - 27) = 0
Factor each set of () completely:
4x^3 - 12x^2 = 4x^2 (x-3)
9x - 27 = 9 (x -3)
So, now you have:
4x^2 (x-3) - 9 (x-3) = 0
Now you can factor out the (x-3) from each term:
(x-3)(4x^2 - 9) = 0
Now, using Difference of Squares, you can better factor the second term:
4x^2 - 9 = (2x-3)(2x+3)
So, you now have:
(x-3)(2x-3)(2x+3) = 0
Set each of those terms =0 and solve for x:
x-3 = 0
x = 3
2x-3 = 0
2x = 3
x = 3/2
2x+3 = 0
2x = -3
x = -3/2
Those are your three answers.
2007-01-11 19:33:01
·
answer #2
·
answered by Mathematica 7
·
0⤊
1⤋
4x^3 - 12x^2 = 9x - 27
factor out common terms from each side
(4x^2) * (x - 3) = 9 * (x - 3)
4x^2 = 9
x^2 = 9/4
take the square root of both sides
x = +/- 3/2
2007-01-11 19:20:12
·
answer #3
·
answered by Anonymous
·
1⤊
3⤋
4x³ - 12 x² = 9x-27
4x²(x - 3) = 9(x - 3)
4x² = 9(x - 3) : (x - 3)
4x² = 9
x = sqrt(9/4)
x' = 3/2 = 1,5
x"= -3/2 = -1,5
Solution: {x elements of R | x = 1,5 or -1,5}
:>:
2007-01-11 19:30:09
·
answer #4
·
answered by aeiou 7
·
0⤊
1⤋
4x(x^2-3x+9)=0
Thats as far as I got, it is prime. You do the math.
2007-01-11 19:24:10
·
answer #5
·
answered by atheist kid 3
·
0⤊
3⤋
Yes.
2007-01-11 19:24:25
·
answer #6
·
answered by Someone who cares 7
·
0⤊
3⤋
4X - 12X= 9X-17 IT WOULD BE 55 (THAT WAS EASY)
2007-01-11 19:22:38
·
answer #7
·
answered by digger 1
·
0⤊
3⤋
True
2007-01-11 19:19:17
·
answer #8
·
answered by Joshm 3
·
0⤊
3⤋
x=a sub n over x
2007-01-11 19:19:18
·
answer #9
·
answered by koolio 2
·
0⤊
3⤋
Nope too hard. Sry.
2007-01-11 19:19:21
·
answer #10
·
answered by fred 2
·
0⤊
4⤋